2018
DOI: 10.1002/hep.30068
|View full text |Cite
|
Sign up to set email alerts
|

CD97 Promotes Tumor Aggressiveness Through the Traditional G Protein–Coupled Receptor–Mediated Signaling in Hepatocellular Carcinoma

Abstract: Cluster of differentiation 97 (CD97) is a member of the epidermal growth factor seven-transmembrane family belonging to the class B G protein-coupled receptors (GPCRs). The protein affects tumor aggressiveness through its cellular ligand CD55 stimulation and exhibits adhesive properties. Studies have demonstrated the involvement of CD97 in dedifferentiation, migration, invasiveness, and metastasis of tumors. However, little information is currently available on the specific role of CD97 in hepatocellular carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…CD97 coupling via G α12/13 has been indicated, involving heterodimerization with the lysophosphatidic acid receptor LPAR1 31 ; and the PTX-sensitive lysophosphatidylethanolamine (LPE) response of LPAR1 in MDA-MB-231 cells requires CD97 42 . GRK6-mediated desensitisation of CD97 33 further indicates its participation in classical GPCR signalling mechanisms. In view of the complexity of interpreting signalling pathways from primary cell data, we were interested to identify defined recombinant systems to investigate aGPCR signalling mechanisms under well-controlled conditions.…”
Section: Discussionmentioning
confidence: 93%
“…CD97 coupling via G α12/13 has been indicated, involving heterodimerization with the lysophosphatidic acid receptor LPAR1 31 ; and the PTX-sensitive lysophosphatidylethanolamine (LPE) response of LPAR1 in MDA-MB-231 cells requires CD97 42 . GRK6-mediated desensitisation of CD97 33 further indicates its participation in classical GPCR signalling mechanisms. In view of the complexity of interpreting signalling pathways from primary cell data, we were interested to identify defined recombinant systems to investigate aGPCR signalling mechanisms under well-controlled conditions.…”
Section: Discussionmentioning
confidence: 93%
“…CD97, which is dependent on interaction with CD55 in order to lead to downstream signalling, is usually internalised following activation by the binding of β‐arrestin‐1, preventing over‐stimulation. However, in HCC, it was found that aberrant internalisation, due to disruption of GRK6‐mediated arrestin binding, leads to overexpression of CD97 and increased secretion of MMP‐2 and MMP‐9 .…”
Section: Regulation Of Mmpsmentioning
confidence: 99%
“…Although CD97 is not directly involved in trophoblast invasion, it reportedly regulates the invasiveness and adhesion of cancer cells [ 31 32 ] . Indeed, another study reported that CD97 stimulated tumor migration via G-protein-coupled receptor-mediated signaling in hepatocellular carcinoma [ 33 ] . Furthermore, CD97 synergistically initiated endothelial cell invasion by co-engaging α5β1 integrin and chondroitin sulfate proteoglycan (CSPG)4 [ 34 ] .…”
Section: Discussionmentioning
confidence: 99%